Omnidirectional Ultra-wideband Superellipse Patch Antenna for mm-Waves Applications - Santos, R. A. dos; Penchel, R. A. [UNESP]; Rehder, G. P.; Spadoti, D. H.; IEEE (Ieee, 2019)
This paper presents an omnidirectional ultra-wideband printed antenna for millimeter waves applications. A novel superellipse based model is proposed to increase the microstrip antenna bandwidth, creating a structure that operates from 46 to 170 GHz. The antenna patch is formed by two halves of superelipse planes, with different smoothing coefficients, optimized to minimize return loss. In order to estimate the electromagnetic performance, a numerical analyzes were performed by ANSYS HFSS, which employs the Finite Element Method (FEM).